2013
DOI: 10.1248/bpb.b13-00123
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Effects of Whole Red Ginseng Extract and Polysaccharide and Saponin Fractions on Influenza A (H1N1) Virus Infection

Abstract: Total extracts of ginseng (the root of Panax ginseng C. A. Meyer) and saponin and polysaccharide fractions have been the main products used to investigate novel effects of ginseng over the last five decades. However, the differences if any between the pharmacological effects of total extract and saponin and polysaccharide fractions are largely unknown. In this study, we compared their effects on influenza A virus infection. Mice received total extract of Korean red ginseng (RG), and polysaccharide and saponin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…25) Not only dietary RG extract but also components of the extract such as polysaccharides and saponin have been reported to increase protection against influenza A virus infection. 26) Moreover, dietary wRG along with xylitol appeared to have a greater protective effect against influenza virus infection than either component alone. 17) Hence the dietary effects of wRG and mixtures of xylitol and wRG were also investigated.…”
Section: Evaluation Of In Vitro Activity Of Xylitol Against Hrsvmentioning
confidence: 97%
“…25) Not only dietary RG extract but also components of the extract such as polysaccharides and saponin have been reported to increase protection against influenza A virus infection. 26) Moreover, dietary wRG along with xylitol appeared to have a greater protective effect against influenza virus infection than either component alone. 17) Hence the dietary effects of wRG and mixtures of xylitol and wRG were also investigated.…”
Section: Evaluation Of In Vitro Activity Of Xylitol Against Hrsvmentioning
confidence: 97%
“…We found no ameliorating effect when xylitol or RGs were administered separately, only when they were given together for 5 days. Since a 14 day-regimen is required for RGs on their own to exert a protective effect on influenza virus infection [11], [12] our results show that the treatment period can be markedly reduced if xylitol is administered along with RGs.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have suggested that components of ginseng can act as inhibitors of influenza virus [10], [11]. We also found that the Korean red ginseng (RG) polysaccharide, saponin, and total extract were effective in reducing flu symptoms when orally administered to mice for 14 days prior to infection [12]. However, the RG extracts were not effective when given for only 5 days.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations